Relationship between Sitting Hours, Physical Activity and Hamstring Flexibility - Purvi Patel; Maitri Shukla (Cutting Edge Research in Biology Vol. 4, 2023)
The hamstring group is an example of a muscle group that is commonly found to be shortened. According to studies, hamstring tightness is caused by extended or prolonged sitting at work and in educational institutions, insufficient physical activity, genetic predisposition, and earlier hamstring injury. Modern sedentary life style is also one of the main reasons for postural abnormality which leads to tightness. It is important to study hamstring flexibility that have long sedentary hours of studying along with lack of physical activities to create awareness about lack of normal flexibility and preventing complications. This chapter consists of discussion on relationship of hamstring flexibility with sitting hours and physical activity. It also contains discussion on possible reasons of the relationship between these factors.